2019
DOI: 10.3390/app9173458
|View full text |Cite
|
Sign up to set email alerts
|

Light Extraction Enhancement of InGaN Based Micro Light-Emitting Diodes with Concave-Convex Circular Composite Structure Sidewall

Abstract: We demonstrate that the concave-convex circular composite structure sidewall prepared by inductively coupled plasma (ICP) etching is an effective approach to increase the light efficiency without deteriorating the electrical characteristics for micro light-emitting diodes (LEDs). The saturated light output power of the device using the concave-convex circular composite structure sidewalls with a radius of 2 μm is 39.75 mW, an improvement of 7.2% compared with that of the device using flat sidewalls. The enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…For example, the sidewall surface of circular blue lLEDs (chip size: 50 lm) was patterned with concave-convex circular composite structures. 104,105 A circular pattern radius of 2 lm was found to be optimal, leading to the highest LEE. This improvement in the LEE was associated with a reduction in the TIR at the sidewall caused by the concave-convex circular composite structure.…”
Section: Efficienct Light Extraction From Lledsmentioning
confidence: 95%
“…For example, the sidewall surface of circular blue lLEDs (chip size: 50 lm) was patterned with concave-convex circular composite structures. 104,105 A circular pattern radius of 2 lm was found to be optimal, leading to the highest LEE. This improvement in the LEE was associated with a reduction in the TIR at the sidewall caused by the concave-convex circular composite structure.…”
Section: Efficienct Light Extraction From Lledsmentioning
confidence: 95%
“…Quantum dots (QDs) have been widely used in photoelectric display, light-emitting diodes, photocatalysis, and other fields [1][2]. However, there are still limitations in stability of color conversion devices prepared by pure QDs [3][4][5]. Therefore, the preparation of color conversion layer by using ordered mesoporous composites (OMMs) combined with quantum dots has become a hot topic in recent years [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, they often suffered from low efficiency [14,15]. There has also been much work to improve the light extraction efficiency (LEE) of the devices and display panels [16][17][18] in order to achieve better external quantum efficiency (EQE). Park et al, from Korea University, reported using indium tin oxide (ITO) as the electrode to form a transparent device, yet it still led to a low current density [19].…”
Section: Introductionmentioning
confidence: 99%